The importance of incorporating systems thinking and One Health in global health classrooms: findings from a One Health simulation activity - Acosta, Daniel; Stark, Heather; Hack, George (Frontiers in Public Health, 2024)
There are several challenges and opportunities in health education in global health. Given the field's rapid expansion, demand for including systems thinking and One Health (a unifying approach that considers human, animal, and environmental health) in global health courses has recently increased. Simulation activities provide an avenue to attain and assess learning objectives that foster critical and systems thinking. This study carried out a One Health simulation activity in an undergraduate global health course, conducted a focus group discussion, and obtained responses from written questionnaires from students who participated in the activity. Data were analyzed using thematic analysis. Results show that the One Health simulation was instrumental for students to understand the complex interactions between different actors and stakeholders in global health systems. The One Health simulation also improved class dynamics, peer-to-peer interactions, and collaborations in the remaining part of the course. The activity helped assess two of the critical thinking learning objectives of the course, and there was some evidence that student agency and confidence may have been improved. Evidence shows that the activity helped students understand the principles of systems thinking and apply them in complex scenarios. Findings support including interactive simulation activities in global health courses to include elements of system science and One Health into classroom activities innovatively and engagingly.